Effects of EFG1 Antisense RNA Expression on Hyphae Formation in Candida Albicans - Tung, Chee Hong (2011)
Candida albicans is a fungus that lives as a commensal in healthy humans. The ability of C. albicans to switch from the yeast to the hyphal form is thought to be crucial in its pathogenesis. Efg1p is one of a number of transcriptional regulators involved in C. albicans yeast to hyphae transition and EFG1 gene null mutants are unable to form hyphae under several hyphae-inducing conditions. Antisense RNA is a relatively new method in C. albicans gene functional studies and was established in a study screening for C. albicans essential genes. Based on the success of the antisense RNA gene silencing method in other fungi, this method has the potential to become a more efficient and effective alternative to the widely used gene deletion method in C. albicans. In this study, an EFG1 antisense RNA expression system was created by cloning the antisense RNA of the EFG1 gene into an expression vector, pGAL1PNiST-1, after a series of restriction enzyme digestion, purification and ligation processes. This recombinant plasmid was designated as pGEFG1, in which the antisense RNA fragment was under the regulation of a GAL1 promoter. Transformation of this plasmid into an auxotrophic C. albicans strain, CAI4,generated a mutant designated as pGCAI4. Microscopic observation comparisons of the pGCAI4 mutants which were incubated under hyphae-inducting conditions in antisense-inducing or antisense-repressing media showed that the hyphae switching ability of the pGCAI4 mutants had not been impaired by the expression of EFG1 antisense RNA. The addition of lithium acetate as an agent to improve the efficacy of the antisense RNA was not feasible due to the interaction between galactose (the antisense-inducing agent for the GAL1 promoter) and lithium acetate, which resulted in the inhibition of hyphae formation. Further analysis using real-time PCR indicated that levels of EFG1 antisense RNA was 4.12-fold higher in the antisense-inducing medium than in the antisense-repressing medium. Hence, this strongly suggests that the EFG1 antisense RNA expression system was functioning in all the conditions tested, albeit not at a sufficient level of expression. Therefore, in an attempt to generate more antisense RNA transcripts in antisense-inducing medium, a stronger regulated promoter, PCK1, was used to replace the original GAL1 promoter in the expression vector. By replacing GAL1 with the new PCK1 promoter, the hyphae switching ability of the newly generated pGPCKCAI4 mutants was found to be impaired, even in hyphae-inducing conditions, after one hr of incubation in antisense-inducing medium, compared to those in antisense-repressing medium. This observation implies that antisense RNA transcript levels could be an influencing factor in knocking down a target gene. However, microscopic observations of the mutant morphologies at two and three hrs after incubation found that the populations of hyphae cells in both media were similar. This observation could be due to three possibilities. Firstly, it has been suggested that Efg1p may only be important in the initiation of hyphae formation, not in later events, as EFG1 is highly expressed during hyphae initiation. Therefore if the level of expressed EFG1 antisense RNA is unable to effectively knock down these endogenous EFG1 transcripts, over time free mRNA may generate sufficient amounts of protein to trigger hyphae growth. Secondly, it is possible that the structures observed at the later time points were pseudohyphae, not true hyphae, as previous studies have found that the morphological forms generated by EFG1 mutants were highly similar to pseudohyphae. Thus, further investigations using electron microscopy and other techniques are required to determine and analyze these structures. Lastly, the serum-induced hyphagenesis pathway may be regulated by several different regulators which appear to act in a cumulative fashion, whereby inactivation of EFG1, depending on a particular set of environmental conditions, may be compensated by alternative pathways. In conclusion, an EFG1 antisense RNA expression system was successfully developed in this study, where an improved PCK1-regulated system successfully expressed sufficient levels of EFG1 antisense RNA to impair the ability of C. albicans to form germ tubes during early hyphae development, thereby delaying the formation of hyphae. This suggests the possible application of this method as an alternative to existing gene knockout methods in gene functional studies of C. albicans morphology switching genes.